Assessment of the quality of accreditation standards for teachers training programs at Saudi Universities in light to the international experiences - Al-Mohayya, Mohammed Ali (Journal of Educational and Psychological Sciences, 2020)
The study aimed to know the accreditation standards for teachers training in United States of America and at Imam Muhammad Bin Saud Islamic University, the study also aimed to know the points of strength and weakness between accreditation standards for teachers training at Imam Muhammad Bin Islamic University and United States of America and preparing a prospective proposal might be used in developing the accreditation standards for teachers training at Imam Muhammad Bin Islamic University in accordance by using the experience of United States of America.The sample of the study consists of (68) participants from faculty member in the department of curricula and teaching methods, PhD holders. This sample has been selected by comprehensive survey, questionnaire tool is used for data collection and analytical descriptive approach used to achieve the objectives of the study.The Results of the Study:- The participants have agreed on the accreditation standards for teacher training at Imam Muhammad Bin Islamic University with average (3.83), also have strongly agreed on the accreditation standards for teacher training in United States of America with average (4.56).The most important strength points of the accreditation standards for teacher training at Imam Muhammad Bin Islamic University based on the following:- The teacher is aware by the different students’ characteristics (abilities, readiness, hobbies and trends) and find the methods of scientific subject.The most important strength points of the accreditation standards for teacher training in United States of America as follow:- Incorruptibility, educational training, experiences, skills, teaching media and information analysis in order to assess the unit and developing its programs.The most important weakness points of the accreditation standards for teacher training at Imam Muhammad Bin Islamic University based on the following:-The teacher’s analysis  materials to the different teaching aspects (concepts, publications, skills), and using different assessment methods for performance assessment.The most important weakness points of the accreditation standards for teacher training in United States of America as follow:- Constitutional assessment, financial sources and presetting a model for professional practices in the search and service.Some recommendations of study:- Necessity attention by the private standards of teacher’s training in Kingdom of Saudi Arabia, and try to increase it due to its decrease compared to the American standards and necessity to using the teacher’s feedback to performance assessment.
Keywords: assessment; teacher’s training programs; Saudis universities; accreditation standards